PENGARUH KESEJAHTERAAN GURU DAN MOTIVASI KERJA TERHADAP PROFESIONALISME GURU - Irawan K, Carrine; Ngurah Ayu Nyoman M; Ghufron Abdullah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
There is often a gap between public and private teachers. Many factors influence and lead to their professionalism as teachers. Professional teachers are needed to improve the quality of education in schools. This study aims to determine the effect of teacher welfare on teacher professionalism, the effect of work motivation on teacher professionalism, and to determine the effect of welfare and work motivation on teacher professionalism in private vocational schools in Bojonegoro district. This research is a quantitative research type with a research sample of 166 private vocational school teachers in Bojonegoro sub-district. The results of the study showed that there was an influence of teacher welfare on teacher professionalism (regression equation Y = 60.087 + 0.312X1, r = 0.561 and contribution of 31.5%); there was an influence of work motivation on teacher professionalism (regression equation Y = 45.625 + 0.827X2, r = 0.639 with contribution of 40.8%.; and there was an influence of teacher welfare, and work motivation on teacher professionalism equation Y = 10.751 + 0.114X1 + 0.377X2, r = 0.689 and contribution of 47.5%). The results of this study provide recommendations to related parties to develop a program for mentoring private teacher professionalism in order to meet the target goals of developing educators and education personnel. Teacher professionalism mentoring will look at factors that increase teacher capacity as professional teachers who have relatively the same opportunities for improving welfare and motivation.